Essential Oil Components, Metabolite Profiles, and Idioblast Cell Densities in Galangal (Kaempferia galanga L.) at Different Agroecology - Subaryanti Subaryanti; Yohana Caecilia Sulistyaningsih; Dyah Iswantini; Triadiati Triadiati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Galangal is widely cultivated for the multifunctional plant. This study analyzed the essential oil chemical components, metabolite profiles, and idioblast cell densities in seven galangal accession grown at two different altitudes (locations A and B). The galangal accessions included: Purbalingga, Cilacap, Purworejo, Karanganyar, Pacitan, Madiun, and Galesia 2 which was used as the control. The results showed that the highest essential oil content was obtained from MAD (3.22%) at location A. The highest levels of ethyl-p-methoxycinnamate (EPMC) were obtained from PBG (74.8%) at location B and PCT (71.6%) at location A. The metabolite profiles of the galangal rhizomes were divided into two clusters based on the metabolite content. The first cluster had one accession: PCT from location A with genkwanin as the metabolite marker. The second cluster consisted of CLP from location A and PBG, MAD, and GAL2 from location B. The highest density of idioblast cells was found in PCT (90.5 cells/mm2) at location A and PBG accessions (77.1 cells/mm2) at location B. The PBG and PCT accessions can be recommended as a candidate of superior varieties based on their high EPMC content.